Puskesmas Accreditation Status And Asset Ownership Potentially Lowering Stunting : Multilevel Analysis In Jeneponto and Barru Districts, South Sulawesi - Munir, Dien Abdul; Hikmayani, Nur Hafidha; Sumardiyono, Sumardiyono (Journal of Health and Nutrition Research, 2025)
The Puskesmas accreditation enhances public health service quality, but its role in stunting prevention is underexplored. Stunting, a critical public health issue, is influenced by healthcare services and socioeconomic factors, including family economic conditions. This study examines the impact of Puskesmas accreditation on stunting prevention in Jeneponto (highest stunting rate) and Barru (lowest stunting rate) in South Sulawesi. Using cross-sectional data from the 2022 Indonesian Nutritional Status Study, analyzed hierarchical data (individual, family, and district levels) comprising 192 mothers, (89 mothers in Jeneponto and 103 in Barru) with infants aged 0–23 months. Descriptive and multilevel binary logistic regression analyses were conducted. At the individual level, stunting was linked to basic education (aOR 3.26; 95% CI: 1.38–7.70) and non-exclusive breastfeeding (aOR 3.64; 95% CI: 1.25–10.6). At the family level, inadequate sanitation (aOR 0.16; 95% CI: 0.03–0.84), higher asset ownership (aOR 0.13; 95% CI: 0.03–0.54). At the district level, Puskesmas accreditation was associated with lower odds of stunting (aOR 0.32; 95% CI: 0.11–0.93). The findings highlight the importance of maintaining Puskesmas accreditation and addressing socioeconomic disparities, such as family economic conditions, to ensure sustainable stunting prevention.